Four strategic functions in corporate diplomacy (Comillas Journal of International Relations, 2017)
Corporate diplomacy is the instrumental development of the strategy building the relationship between public and private powers in a complex and globalized environment. International companies act as diplomatic powers in the representation, negotiation, protection and promotion of their self-interests, the four basic functions of diplomacy established by the Vienna Convention in 1961. The task of corporate diplomacy is a source of innovation management and an opportunity for professional development.
Keywords: corporate diplomacy; lobby; international communication; globalization